Can Purple Sweet Potato Water Extract (Ipomoea batatas L.) Induce Steatosis at Toxic Doses in Rat? - Hikmatussalam, Gemila; Kharisma, Yuktiana; Romadhona, Nurul (Jurnal Kesehatan Andalas, 2023)
Purple sweet potato (Ipomoea batatas L.) has a secondary metabolite that contains a lot of antioxidants. Some of the secondary metabolites in purple sweet potato have a hepatotoxic effect. Objective: To described the toxic effects of purple sweet potato water extract on steatosis in rats. Methods: This descriptive study was conducted on 29‒30 June 2019 in the Biomedical Laboratory of the Faculty of Medicine, Islamic Bandung University, with an in-vivo experimental design with random allocation techniques and using the proposed new method on 11 rats. One of the control rats was not given extract, and ten other rats were given a dose of purple sweet potato water extract 50, 200, 400, 800, 1000, 1500, 2000, 3000, 4000, and 5000 mg/KgBW/PO. The liver organ was harvested after 24 hours, and then slides were made at the Pathology Anatomy Laboratory of Padjajaran University. Results: The histopathological view did not find any steatosis either in macrovesicular or microvesicular, but other features were found in ballooning degeneration, sinusoidal dilation, and inflammation. Conclusion: Steatosis was not found because purple sweet potato contains anthocyanins and tannins.Keywords: purple sweet potato, steatosis, tannin